2006
DOI: 10.1002/sca.4950280101
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol crystals rupture biological membranes and human plaques during acute cardiovascular events‐a novel insight into plaque rupture by scanning electron microscopy

Abstract: Plaque rupture and/or erosion are considered the leading cause of cardiovascular events. To elucidate this process, we demonstrated that during cholesterol crystallization the occupied volume increases rapidly and sharp-tipped crystals cut through thin biological membranes in their path. The amount of cholesterol correlated directly with both peak level and rate of crystal growth (r = 0.98; r = 0.99; p < 0.01, respectively). These observations suggest that crystallization of cholesterol in atherosclerotic plaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 30 publications
1
84
0
Order By: Relevance
“…In contrast, previous studies concluded that CholM crystals were present in ruptured human (41) and rabbit plaques (42) by the indirect observation of "cholesterol clefts." Abela and Aziz (43) showed that during cholesterol crystallization, the expansion of sharpedged crystals could damage the fibrous cap.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies concluded that CholM crystals were present in ruptured human (41) and rabbit plaques (42) by the indirect observation of "cholesterol clefts." Abela and Aziz (43) showed that during cholesterol crystallization, the expansion of sharpedged crystals could damage the fibrous cap.…”
Section: Discussionmentioning
confidence: 99%
“…IP 3 binds to and opens the IP 3 receptor embedded in the endoplasmic reticulum (ER) membrane, releasing into the cytoplasm calcium stored in the ER. Free calcium can bind calmodulin (CaM) and many other effectors.…”
Section: Other Adapters and Enzymes Link Insr To Multiple Pathwaysmentioning
confidence: 99%
“…Novel PKC enzymes (PKC␦, -, -, and -) are activated by DAG but not calcium. Atypical PKCs, including PKC, -, and -, can be activated by PIP 3 or ceramide. All the PKC enzymes are further activated by PDK1 in PIP 3 -enriched cell membranes.…”
Section: Other Adapters and Enzymes Link Insr To Multiple Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations